Molecular structure of the phosphate mineral koninckite - a vibrational spectroscopic study - Jirasek,J.; Cejka,J.; Vrtiska,L.; Matysek,D.; Ruan,X.; Frost,R.L. (Journal of Geosciences, 2017)
We have undertaken a study of the mineral koninckite from Litosice (Czech Republic), a hydrated ferric phosphate, using a combination of scanning electron microscopy with electron probe micro-analyzer (wavelength-dispersive spectroscopy) and vibrational spectroscopy. Chemical analysis shows that studied koninckite is a pure phase with an empirical formula Fe3+0.99(PO4)1.00∙2.75 H2O, with minor enrichment in Al, Ca, Ti, Si, Zn, and K (averages 0.00X apfu). Raman bands and shoulders at 3495, 3312, 3120, and 2966 cm-1 and infrared bands and shoulders at 3729, 3493, 3356, 3250, 3088, 2907, and 2706 cm-1 are assigned to the ν OH stretching of structurally distinct differently hydrogen bonded water molecules, A Raman band at 1602 cm-1 and shoulders at 1679, 1659, 1634, and 1617 cm-1 and infrared bands at 1650 and 1598 cm-1 are assigned to the ν2 (δ) H2O bending vibrations of structurally distinct differently hydrogen bonded water molecules. Raman shoulders at 1576, 1554, 1541, 1532, and 1520 cm-1 and infrared shoulders at 1541 and 1454 cm-1 may be probably connected with zeolitically bonded water molecules located in the channels. Raman bands and shoulders at 1148, 1132, 1108, 1063, 1048, and 1015 cm-1 and an infrared band and shoulders at 1131, 1097, 1049, and 1017 cm-1 are assigned to the ν3 PO43- triply degenerate antisymmetric stretching vibrations. A Raman band and a shoulder at 994 and 970 cm-1, respectively, and an infrared band and a shoulder at 978 and 949 cm-1, respectively, are assigned to the ν1 PO43- symmetric stretching vibrations. Infrared shoulders at 873, 833, and 748 cm-1 are assigned to libration modes of water molecules. Raman bands and shoulders at 670, 648, 631, 614, 600, 572, and 546 cm-1 and infrared bands at 592 and 534 cm-1 are assigned to the ν4 (δ) PO43- triply degenerate out-of-plane bending vibrations; weak band at 570 cm-1 may coincide with the δ Fe-O bending vibration. Raman bands and shoulders at 453, 443, 419, and 400 cm-1 are assigned to the ν2 (δ) PO43- doubly degenerate in-plane bending vibrations. Raman bands at 385, 346, 324, 309, 275, 252, and 227 cm-1 are assigned to the ν Fe-O stretching vibrations in FeO6 octahedra. Raman bands at 188, 158, 140, 112, 89, and 73 cm-1 are assigned to lattice vibrations.
Keywords: koninckite; phosphate; Raman spectroscopy; infrared spectroscopy